1983
DOI: 10.1002/ajh.2830150206
|View full text |Cite
|
Sign up to set email alerts
|

Diminished adherence of sickle erythrocytes to cultured vascular endothelium by piracetam

Abstract: Erythrocytes from both normal and sickle cell donors were incubated on a bed of cultured rat vascular endothelial cells. Although the adherence of the erythrocytes to the endothelial cells was equivalent for both classes of donor, addition of 1.5 mM piracetam significantly decreased this adherence regardless of donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Reduced erythrocyte adhesion to the endothelial wall following piracetam administration was reported by Nalbandian and colleagues (57). Blood taken from healthy individuals and from those with sickle cell anemia was incubated with saline or 1.5 mmol/L of piracetam for at least 30 min prior to additional incubation with endothelial cell culture (57).…”
Section: Effects On Erythrocytesmentioning
confidence: 87%
See 2 more Smart Citations
“…Reduced erythrocyte adhesion to the endothelial wall following piracetam administration was reported by Nalbandian and colleagues (57). Blood taken from healthy individuals and from those with sickle cell anemia was incubated with saline or 1.5 mmol/L of piracetam for at least 30 min prior to additional incubation with endothelial cell culture (57).…”
Section: Effects On Erythrocytesmentioning
confidence: 87%
“…Studies suggest that piracetam exerts a number of effects on erythrocytes, such as decreased adhesion to endothelium (57). These effects are likely to facilitate movement of erythrocytes through the circulation.…”
Section: Effects On Erythrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…6. Влияние на сосудистые механизмы ■ Уменьшение адгезии эритроцитов к эндотелию стен-ки сосудов [21]. ■ Влияние на сосудистую стенку.…”
Section: влияние на энергетический обмен в клеткеunclassified
“…Similarities between the vaso-occlusive crisis and senile vasculopathy, and between piracetam, a cyclic derivative of γ-aminobutyric acid, and urea led to studies on piracetam in sickle cell disease. Most of the in vitrostudies with piracetam, performed mainly during the period of 1974–1992, have shown a reversal of sickling, a reduction in blood viscosity, an increase in erythrocyte elasticity, a reduction in adherence to the vascular endothelium, inhibition of platelet aggregation, water reduction and cell potassium loss [14,15,16,17,18,19]. An in vitro study performed in 1979 showed the drug to be ineffective [20].…”
Section: Introductionmentioning
confidence: 99%